Rolled copper foil, copper-clad laminate, method for manufacturing copper-clad laminate, method for manufacturing flexible printed wiring board, and method for manufacturing electronic component
By controlling the Taylor factor and alloy elements in the rolled copper foil, the problem of insufficient bending in the prior art is solved, and higher bending and stability are achieved, meeting the needs of electronic devices such as smartphones.
Patent Information
- Application Number
- CN202380042417.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-04
- Filing Date
- 2023-06-01
- Publication Date
- 2025-01-03
AI Technical Summary
With the trend of thinness and shortness of electronic devices such as smartphones, the existing rolled copper foil cannot meet the increasingly strict bending requirements, resulting in insufficient bending and unable to meet market demand.
By performing heat treatment on the calendered copper foil, the Taylor factor is controlled to be less than 2.485, and the appropriate amount of Ag alloy elements and the control of crystal grain size are improved.
It achieves higher bending properties during the FPCization process, improves the bending resistance and stability of the rolled copper foil, and meets the market's demand for higher bending properties.
Smart Images

Figure BDA0005148581480000161 
Figure BDA0005148581480000181 
Figure HDA0005148581500000011
Abstract
Description
Technical Field
[0001] The present invention relates to a rolled copper foil, a copper-clad laminate, a method for manufacturing a copper-clad laminate, a method for manufacturing a flexible printed wiring board, and a method for manufacturing an electronic component. Background Art
[0002] Flexible printed circuit boards (FPCs) are made by bonding a metal conductive layer to a flexible insulating substrate represented by a resin film. Usually, copper foil is used for the conductive layer, and in applications where flexibility is particularly required, rolled copper foil having excellent flexibility is used.
[0003] The usual FPC manufacturing steps are as follows. First, copper foil is bonded to a resin film. Regarding bonding, there is a method of coating a varnish containing a precursor of a polyimide resin on the copper foil and applying a heat treatment to imidize it (casting method), and a method of overlapping and laminating a resin film having adhesiveness with the copper foil (lamination method). The copper foil with a resin film bonded by these steps is called a copper clad laminate (CCL). After that, wiring is formed by etching to complete the FPC.
[0004] As mentioned above, the rolled copper foil for FPC requires bendability. In order to provide a rolled copper foil for FPC that is easy to anneal at the curing temperature of the resin adhesive and has excellent bending resistance (bending fatigue life) after annealing, it is proposed to make the final cold working degree 90% or more.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent document 1: Japanese Patent Application Publication No. 4-228553. Summary of the invention
[0008] Technical problem to be solved by the invention
[0009] However, as electronic devices such as smartphones have become thinner, shorter, and more functional in recent years, the bendability required of rolled copper foil has become increasingly stringent. As a result, copper foil produced using existing technologies is no longer able to meet customer needs.
[0010] Therefore, in one embodiment of the present invention, an object is to provide a rolled copper foil having higher bendability than ever before when converted into an FPC.
[0011] Solutions to technical problems
[0012] The present inventors have conducted various studies and found that a rolled copper foil having high bendability can be obtained by setting the Taylor factor of the rolled copper foil to 2.485 or less when the rolled copper foil is heat treated under predetermined conditions, and have created the invention as exemplified below. [1]
[0014] A rolled copper foil containing 99.9 mass % or more of Cu, the remainder being composed of inevitable impurities, wherein when the rolled copper foil is heat treated at a temperature in a dryer of 260° C. and a heating holding time of 30 minutes, the arithmetic mean value of the Taylor factor measured at a total of three points, namely, one arbitrary point and two points each equally spaced 5 mm from the point in a direction perpendicular to the rolling, is 2.485 or less. [2]
[0016] The rolled copper foil as described in [1] further contains 100 to 360 mass ppm of Ag. [3]
[0018] The rolled copper foil as described in [1] or [2] has a thickness of 4 to 35 μm. [4]
[0020] The rolled copper foil according to any one of [1] to [3], wherein the arithmetic mean of the Taylor factor is 2.300 or more. [5]
[0022] A copper-clad laminate having a rolled copper foil having an arithmetic mean value of Taylor factors measured at an arbitrary point and two points equally spaced 5 mm from the point in a direction perpendicular to the rolling, i.e., a total of three points, of 2.485 or less. [6]
[0024] The copper-clad laminate as described in [5] has a rolled copper foil whose arithmetic mean value of the Taylor factor is 2.300 or more. [7]
[0026] A method for producing a copper-clad laminate, comprising: bonding the rolled copper foil described in any one of [1] to [4] to a substrate, and performing a heat treatment in the step. [8]
[0028] A method for manufacturing a flexible printed wiring board, comprising the steps of using the copper-clad laminate board manufactured by the method for manufacturing a copper-clad laminate board described in [7] as a material and forming wiring. [9]
[0030] A method for manufacturing an electronic component includes: a step of manufacturing an electronic component, wherein the electronic component includes a flexible printed wiring board manufactured by the method for manufacturing a flexible printed wiring board according to [8].
[0031] Effects of the Invention
[0032] According to one embodiment of the present invention, it is possible to provide a rolled copper foil having higher bendability than ever before when converted into an FPC. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram showing the measurement method of the IPC sliding bending test in Example 5 and Comparative Examples 4 and 5.
[0034] Figure 2 This is a graph plotted based on Example 5 and Comparative Examples 4 and 5, with the horizontal axis representing the arithmetic mean of the Taylor factor after heat treatment at 260° C. for 30 minutes and the vertical axis representing the IPC sliding bending number.
[0035] Description of Reference Numerals
[0036] 10: Vibration drive body
[0037] 20: Vibration transmission parts
[0038] 30: Test piece
[0039] 40: Screw
[0040] 100: IPC bending test device
[0041] r: radius of curvature. DETAILED DESCRIPTION
[0042] The present invention is not limited to the embodiments described below, and the components can be modified and embodied within the scope of the gist thereof. In addition, various inventions can be formed by appropriately combining a plurality of components disclosed in the embodiments.
[0043] In addition, the "Taylor factor" in this specification means the total amount of crystal shear due to slip deformation that must be active in order to generate unit strain by rolling.
[0044] In addition, the "rolling direction" refers to a direction parallel to the direction in which the rolled object passes between the pair of work rolls. Furthermore, the "rolling perpendicular direction" refers to a direction perpendicular to the rolling direction in the rolling surface.
[0045] [1. Rolled copper foil]
[0046] (Component)
[0047] In one embodiment, the rolled copper foil of the present invention contains 99.9 mass % or more of Cu, with the remainder being composed of inevitable impurities. In another embodiment, the rolled copper foil may be composed of pure Cu.
[0048] In another embodiment, the rolled copper foil may contain 100 to 360 ppm by mass of Ag as an alloy element from the viewpoint of more reliably obtaining higher bendability than before when FPC-formed and controlling the appropriate recrystallization temperature. In particular, it is preferred that the above-mentioned additive element be contained in tough pitch copper (TPC) of JIS H 3100 (C1100) or oxygen-free copper (OFC) of JIS H 3100 (C1020).
[0049] When the Ag concentration is greater than 360 mass ppm, the recrystallization temperature of the rolled copper foil increases, and even if the heat treatment in the casting method or lamination method is performed, the recrystallization is sometimes insufficient. If it is assumed that there are unrecrystallized grains remaining in the rolled copper foil, the bendability of the FPC will be significantly reduced. In addition, if the Ag concentration is greater than 100 mass ppm, the amount of rolling strain introduced will increase, so the grains after the CCL heat treatment grow larger, and the Taylor factor can be controlled within the specified range, so the bendability is easily increased.
[0050] In addition, the upper limit of the oxygen content in the rolled copper foil is, for example, 500 mass ppm or less. In addition, the lower limit of the oxygen content in the rolled copper foil is, for example, 0 mass ppm or more. Based on the viewpoint of reducing the amount of copper oxide (CuO) in the material, the oxygen content is preferably 50 mass ppm or less, and copper oxide (CuO) is generally considered to have an adverse effect on the bendability of the FPC.
[0051] The composition of the rolled copper foil of the present invention can be measured by fluorescent X-ray analysis as a dry analysis. Specifically, the fluorescent X-ray analysis is measured using Simultix14 manufactured by Rigaku Corporation. The analysis surface can use a surface that has been cut or mechanically polished in a manner such that the surface maximum height roughness Rz (JIS B0601: 2013) is 6.3 μm or less. In the case of taking a sample for analysis from the molten metal in the melt casting process of the manufacturing process of the rolled copper foil, it is cast into a shape of 30 to 40 mmΦ and a thickness of about 50 to 80 mm, and then cut into a thickness of about 10 to 20 mm, and the cut surface is used as the analysis surface. The analysis surface is repeatedly cut or mechanically polished until the surface maximum height roughness Rz (JIS B0601: 2013) is 6.3 μm or less.
[0052] In addition, the composition of the rolled copper foil can be determined by using fluorescent X-ray analysis or ICP emission spectrometry as a wet analysis. Specifically, the ICP emission spectrometry device (ICP-OES) SPS3100 manufactured by Hitachi High-Tech Sciences can be used for measurement. In the case of ICP emission spectrometry, the sample is dissolved in a nitric acid aqueous solution (nitric acid: water = 1:1 by volume ratio) and diluted for use.
[0053] (Taylor Factor)
[0054] In one embodiment of the rolled copper foil of the present invention, when the rolled copper foil is heat-treated at a temperature in a dryer of 260°C and a heating holding time of 30 minutes, the arithmetic mean value of the Taylor factor is 2.485 or less when measured by the method described below. Specifically, a portion of the rolled copper foil is taken as a sample, and the sample is placed in a dryer (DRH453WA manufactured by Advantech Toyo Co., Ltd.) maintained at 260°C, and after heat treatment for 30 minutes in the air, the sample is taken out of the dryer and left to cool in the air. In addition, in order to prevent oxidation in the air or to prevent bending and wrinkling when the sample is taken out of the dryer, the rolled copper foil is sandwiched between two phosphor bronze (JIS H3110 (C5210)) plates (thickness: 0.2mm) to form a laminate, and then the laminate is wrapped with a rolled copper foil (thickness: 33μm) of tough copper that has been fully annealed to form a sealed body, and then placed in the dryer.
[0055] The rolled copper foil whose surface Taylor factor under the prescribed heat treatment conditions is within the prescribed range can be deformed mainly by uniform slip deformation even without the assistance of deformation caused by shear bands during bending, so the accumulation of dislocation strain accompanying the deformation is difficult to occur. As a result, the generation of cracks that cause rupture is suppressed, so the bendability is excellent, for example, stable bendability that does not depend on the heating conditions when manufacturing copper-clad laminates can be obtained. The upper limit side of the arithmetic mean of the above-mentioned Taylor factor is less than 2.485. On the other hand, the lower limit side of the arithmetic mean of the above-mentioned Taylor factor is preferably greater than 2.300. When the arithmetic mean of the Taylor factor is too small, when used as an FPC and bent, strain is easily generated in the copper foil, which will have an adverse effect on the bendability.
[0056] Therefore, the inventors have found that in order to control the arithmetic mean value of the Taylor factor after heat treatment within a specified range, the control of the average grain size after final annealing and the processing degree of final cold rolling are very important. The conditions of the average grain size after final annealing and the processing degree of final cold rolling are described below and will not be repeated.
[0057] (Method for determination of Taylor factor)
[0058] Next, an example of the method for measuring the Taylor factor is described. The Taylor factor is measured by EBSD on the surface of the rolled copper foil sample after heat treatment at 260°C for 30 minutes as described above. Here, EBSD (Electron Back Scatter Diffraction) refers to a technique for analyzing the crystal orientation using the reflected electron Kikuchi line diffraction (Kikuchi pattern) generated when an electron beam is irradiated on a sample in a SEM (Scanning Electron Microscope).
[0059] Electrolytic polishing was performed according to the following electrolyte and test conditions. After removing a thickness of about 1 μm from the sample surface, an observation range of 1000 μm×1000 μm arbitrarily set in a manner with one side of the observation field parallel to the rolling direction was scanned with a step size of 3 μm to measure the crystal orientation distribution.
[0060] The measurement is carried out at any one point and two points, i.e., three points in total, which are equally spaced 5 mm from the point in the direction perpendicular to the rolling. In addition, if the arithmetic mean of the Taylor factor measured at any one point and two points, i.e., three points in total, which are equally spaced 5 mm from the point in the direction perpendicular to the rolling is 2.485 or less, the rolled copper foil as a whole tends to have high bendability. The reason is that, although the manufacturing conditions may have some deviations to a certain extent in the manufacturing step, after the rolled copper foil obtained by the manufacturing step is subjected to heat treatment under prescribed conditions, the measured Taylor factor is roughly controlled within the required range. Therefore, when the arithmetic mean of the Taylor factor measured at any one point and two points, i.e., three points in total, which are equally spaced 5 mm from the point in the direction perpendicular to the rolling is 2.485 or less, although there is a possibility that a portion of the rolled copper foil has a Taylor factor with an arithmetic mean greater than 2.485, it can be assumed that there are not so many such portions, and most of them become the required metal structure, which can solve the technical problem of the present invention.
[0061] Furthermore, due to manufacturing and rolling processes of copper foils (e.g., cutting of specimens for measurement, etc.), there will be some positions with extremely many holes, abnormal areas with foreign matter attachment, rolling streaks, etc. When measuring the Taylor factor, the measurement positions should be set avoiding the positions corresponding to the abnormal areas. By observing the specimen before electropolishing using SEM (observation magnification: 100 times), the abnormal areas can be grasped. When the above-mentioned measurement positions overlap with the abnormal areas, measurements are taken at a total of 3 points while avoiding the abnormal areas.
[0062] <Formulation of electrolyte (an example)>
[0063] · 250 ml of distilled water
[0064] · 125 ml of phosphoric acid
[0065] · 2.5 g of urea
[0066] · 125 ml of grade 1 ethanol
[0067] · 25 ml of 1-propanol
[0068] <Electropolishing conditions>
[0069] Applied voltage: 10 V
[0070] Electrolysis time: 10 seconds
[0071] <Measurement conditions of EBSD, etc.>
[0072] · SEM conditions
[0073] Device: Scanning electron microscope manufactured by JEOL Ltd. (JSM-IT500HR or an equivalent device)
[0074] Type of electron gun: Field emission type electron gun (Schottky type)
[0075] Emitter of electron gun: ZrO tungsten cathode
[0076] Type of objective lens: External lens type
[0077] Presence or absence of focus correction: Yes (Dynamic focus: 50)
[0078] Electron beam conditions
[0079] Accelerating voltage: 15 kV
[0080] Working distance: 15 mm
[0081] Irradiation current: 15 nA
[0082] SEM probe diameter: 0.5 - 2 nm
[0083] Observation magnification: 90 times
[0084] ·EBSD device conditions
[0085] Detector: Slow-scan CCD camera manufactured by TSL Solutions Co., Ltd.
[0086] Data processing conditions
[0087] Data collection software: OIM Data Collection manufactured by TSL Solutions Co., Ltd. Phase: Copper
[0088] CCD camera pixel count: 1394 × 1040 pixels
[0089] Binning (pixel combination): 8×8
[0090] Exposure: 8 milliseconds
[0091] Gain: 0.9~0.95
[0092] Background processing: Yes
[0093] Scanning method of measuring points: Hexagonal grid
[0094] Hough transform
[0095] (1) Hough Type: Classic
[0096] (2) Hough Resolution: Low
[0097] (3) Classic Hough
[0098] Convolution Mask: 9×9
[0099] Min Peak Magnitude: 5
[0100] Min Peak Distance: 23
[0101] Peak Symmetry: 0.75
[0102] Vertical Bias: 0
[0103] (4) General Parameter
[0104] ·Binned Pattern Size: 120
[0105] ·Theta Step Size: 1°
[0106] ·Rho Fraction: 90%
[0107] ·Max Peak Count: 8
[0108] ·Min Peak Count: 3
[0109] The above measurement data was collected using OIM Data Collection manufactured by TSL Solutions Co., Ltd., and the data analysis was performed using OIM Analysis V8 manufactured by TSL Solutions Co., Ltd.
[0110] <Data Analysis Conditions of OIM Analysis V8>
[0111] ·New Map window
[0112] Map type
[0113] Grayscale: Selected <none>.
[0114] Color Coded: Select <none>.
[0115] Second Partition: Select <none>.
[0116] Taylor Factor window (the interface displayed when clicking Edit in Color Coded in the Map Style window)
[0117] Edit window (the interface that appears if you click Add next to the Type selection bar)
[0118] Taylor Factor Tags
[0119] Phase: Select Copper.
[0120] Slip System window (the screen that appears when you click Add under the Phase selection bar)
[0121] Input values of hkl: 111
[0122] Input values of uvw: 1-10
[0123] CRSS value: 0.2
[0124] Deformation Gradient Window
[0125] X-axis values: 1, 0, 0
[0126] Y-axis values: 0, -0.5, 0
[0127] Z-axis values: 0, 0, -0.5
[0128] Range Tag
[0129] Method: Check the radio button for Percentage
[0130] Minimum input value (minimum input value): 0
[0131] Maximum input value (maximum input value): 100
[0132] Parameters Tab
[0133] Number of bins value: 20
[0134] Vertical Axis: Check the Number Fraction radio button.
[0135] The area average value among the measurement results of Taylor Factor carried out under the above-mentioned setting conditions was used as the Taylor factor.
[0136] (Average grain size after final annealing)
[0137] In one embodiment of the rolled copper foil of the present invention, the average grain size before the final cold rolling and after the recrystallization annealing 3 (final annealing) in the manufacturing example described below is preferably greater than 15 μm and less than 35 μm. Generally, the smaller the grain size, the easier it is to accumulate the dislocation strain that becomes the driving force of the primary recrystallization during the final cold rolling. Therefore, by making the average grain size before the final cold rolling and after the final annealing greater than 15 μm and less than 35 μm, the arithmetic mean of the Taylor factor during the heat treatment of the rolled copper foil will be within the specified range, thereby improving the bendability. On the other hand, when the average grain size after the final annealing is greater than 35 μm, the dislocation strain is not easy to accumulate during the final cold rolling, and the shear band in the rolled structure is easy to become developed. The presence of shear bands will make the Taylor factor easy to become too large during the heat treatment of the rolled copper foil.
[0138] (Method for measuring average crystal grain size)
[0139] Next, an example of a method for measuring the average grain size is described. The average grain size is measured by EBSD on the surface of the sample after the final annealing.
[0140] Electropolishing was performed under the above conditions. After removing a thickness of about 1 μm from the sample surface, the observation range of 1000 μm × 1000 μm was arbitrarily set and scanned with a step size of 3 μm. After that, the average grain size when the boundary with a crystal orientation difference greater than 5° was regarded as a crystal grain boundary was measured by the Area Fraction method. The above analysis was performed using OIM Analysis V8 manufactured by TSL Solutions Co., Ltd. The measurement conditions of EBSD not shown below are as described above.
[0141] <Detailed settings of OIM Analysis V8 for calculating average grain size>
[0142] ·Detailed settings of the Partition Properties window
[0143] Grain Size Tab
[0144] Input value for Grain Tolerance Angle: 5
[0145] Minimum Size [points]
[0146] Grains input value: 2
[0147] Anti-grains input value: 2
[0148] Input value for Minimum Confidence Index (minimum CI value): 0
[0149] Check the box for Apply partition before calculation: Check √.
[0150] Include grains at edges of scan in statistics check box: Check √.
[0151] Twin Boundaries window (displayed when you click Define in Partition Properties)
[0152] Check the box for Enforce matching between twin planes(K1)in grain A and grain B: Check √.
[0153] Allowed tolerance between twin planes (K1s)[degrees] Input value: 1
[0154] (Twins that are excluded are not specifically specified. Crystal grain boundaries include twins.)
[0155] ·Detailed settings of the New Chart window for calculating the average grain size Type: Grain Size (diameter)
[0156] In the measurement results of Grain Size performed under the above-mentioned setting conditions, the value of Area within Average (average value according to the Area Fraction method) is used as the average crystal grain size.
[0157] (thickness)
[0158] In one embodiment, the rolled copper foil has a thickness of 4 to 35 μm, for example. The upper limit of the rolled copper foil thickness is, for example, 35 μm or less, or 18 μm or less, and the lower limit is, for example, 4 μm or more, or 6 μm or more, or 9 μm or more.
[0159] The thickness of the rolled copper foil can be measured by, for example, setting an X-ray generator on the surface side of the rolled copper foil and setting an X-ray detector on the front side of the other side, calculating the attenuation caused by the rolled copper foil based on the measured amount of penetrating X-rays, and converting it into the thickness of the rolled copper foil. For example, the weight of a 20 cm square rolled copper foil is measured and the value is calculated by (weight (g) / (density of rolled copper foil (g / cm 3 )×Area of rolled copper foil (cm 2 )) Calculate the thickness of the rolled copper foil (In addition, the density of the rolled copper foil, as an example, JIS H 3100 (C1020) oxygen-free copper is 8.94 g / cm 3 ). For another example, a digital length measuring machine (as an example, a Nikon-made Micro Digital MH-15M) is used to measure at two or more points, and the thickness of the rolled copper foil is calculated from the arithmetic mean of the thicknesses.
[0160] (Manufacturing Example of Rolled Copper Foil)
[0161] As an example of a method for manufacturing rolled copper foil, first, a melting furnace is used to melt raw materials such as copper to obtain a molten metal of the required components. Then, an ingot is manufactured by flowing the molten metal into a mold (casting). In order to prevent oxidation loss of copper, melting and casting are preferably carried out in a vacuum or inert gas atmosphere. Afterwards, the following steps are implemented in sequence: homogenization annealing, hot rolling, cold rolling 1, recrystallization annealing 1, surface cutting, cold rolling 2, recrystallization annealing 2, pickling and grinding, cold rolling 3, recrystallization annealing 3 (final annealing), and final cold rolling to form a rolled copper foil having the required thickness and the required characteristics. That is, in the present invention, the rolled copper foil can be said to basically refer to the copper foil after the final cold rolling.
[0162] It should be noted that according to the empirical speculation of the inventors, the arithmetic mean value of the Taylor factor of the rolled copper foil when subjected to a heat treatment at 260°C for 30 minutes is greatly affected by the average grain size after the final annealing and the degree of processing of the final cold rolling when the rolled copper foil is manufactured according to the steps described below.
[0163] (Final Annealing)
[0164] In order to control the arithmetic mean value of the Taylor factor when the heat treatment is performed at 260°C for 30 minutes within a specified range, the conditions of the final annealing are appropriately set. Specifically, the conditions of the final annealing can be appropriately set so that the average grain size after the final annealing is greater than 15 μm and less than 35 μm. The conditions can be changed according to the composition of the copper material. Based on the annealing conditions disclosed in the present embodiment and the comparative example, those skilled in the art can experimentally determine the annealing conditions without too much trial and error.
[0165] (Final cold rolling)
[0166] By performing the final cold rolling under the condition of a processing degree greater than 98% and less than 99%, a rolled copper foil can be obtained. At this time, the thickness of the rolled copper foil is about 4 to 35 μm. In addition, the processing degree is defined as processing degree (%) = {(thickness before final cold rolling (mm) - thickness after final cold rolling (mm)) / thickness before final cold rolling (mm)} × 100.
[0167] [2. Method for manufacturing copper-clad laminate]
[0168] In one embodiment of the method for manufacturing a copper-clad laminate of the present invention, the method comprises the step of bonding the rolled copper foil as described above to a substrate. As the substrate, for example, a resin film can be cited. In order to bond the resin film to the rolled copper foil, several methods can be used.
[0169] For example, the following method can be used: using an adhesive formed of a thermosetting resin such as an epoxy resin, the rolled copper foil and the polyimide resin film are bonded together and heat-treated. Alternatively, the following method can be used: applying a varnish containing polyamic acid, which is a precursor of the polyimide resin, on at least one surface of the rolled copper foil and heat-curing it to form a polyimide coating on at least one surface of the rolled copper foil.
[0170] In the case of double-sided rolled copper foil, there is a method of forming a single-sided copper-clad laminate and then pressing the rolled copper foil by hot pressing, and a method of sandwiching a polyimide resin film between two copper foil layers and pressing them by hot pressing. These heat treatments are usually carried out under the conditions of 125 to 360°C and 30 to 400 minutes.
[0171] Furthermore, there is also a method of laminating the rolled copper foil and the resin film by using an adhesive without the heat treatment step. As the material of the resin film, polyester, polyimide, polyethylene terephthalate, polyethylene naphthalate, etc. can be listed, but it is not limited to these.
[0172] In addition, the rolled copper foil may be subjected to a roughening treatment before laminating the rolled copper foil and the resin film. This can improve the bonding strength between the resin film and the rolled copper foil. For example, the roughening treatment can be performed under the following conditions.
[0173] <Roughening Treatment Conditions>
[0174] Liquid components: Cu 10~20g / L, Co 1~10g / L, Ni 1~15g / L
[0175] pH: 1-4
[0176] Temperature: 30~50℃
[0177] Current density (Dk): 20~50A / dm 2
[0178] Time: 1 to 5 seconds
[0179] According to the manufacturing method, a copper-clad laminate having a copper foil (rolled copper foil) and a substrate (resin film) can be manufactured by the above-mentioned heat treatment, and the arithmetic mean of the Taylor factor measured at any one point of the copper foil and two points in the vertical direction of rolling and equidistant from the point by 5 mm, i.e., a total of three points, is 2.485 or less. In addition, the method for measuring the Taylor factor is the same as the method described above.
[0180] [3. Method for manufacturing flexible printed wiring board]
[0181] In one embodiment, the method for manufacturing a flexible printed wiring board of the present invention includes using a copper-clad laminate manufactured by the method for manufacturing a copper-clad laminate as described above as a material and forming wiring. At this time, the copper-clad laminate can be used as a material and wiring can be formed according to known steps to manufacture a flexible printed wiring board (FPC). For example, the following method can be cited: on the rolled copper foil surface of the copper-clad laminate, an etching agent is applied only to the necessary part as a conductor pattern, and then an etching solution is sprayed on the rolled copper foil surface to remove unnecessary rolled copper foil to form a conductor pattern, and then the etching agent is peeled off or removed to expose the conductor pattern. After the conductor pattern is formed, a protective covering film is usually attached.
[0182] (use)
[0183] Such an FPC is an FPC used in a movable part in a hard disk, a hinge part and a sliding part of a mobile phone, the inside of a mobile phone, a head of a printer, an optical pickup part, a movable part of a notebook PC, etc. in an electronic component of an electronic device or an electrical device. In addition, the method for manufacturing an electronic component may include a step of manufacturing an electronic component having a flexible printed wiring board manufactured by the method for manufacturing a flexible printed wiring board.
[0184] [Example]
[0185] The present invention will be specifically described based on Examples and Comparative Examples. The following Examples and Comparative Examples are only specific examples given to facilitate understanding of the technical content of the present invention, and the technical scope of the present invention is not limited to these specific examples.
[0186] In Tables 1 and 2, "OFC" refers to oxygen-free copper in accordance with JIS H 3100 (C1020), and "TPC" refers to tough pitch copper in accordance with JIS H3100 (C1100).
[0187] [Examples 1 to 4 and Comparative Examples 1 to 3]
[0188] [Manufacture of rolled copper foil]
[0189] First, in Examples 1 to 4 and Comparative Examples 1 to 3, an ingot is melted and cast, and the ingot has an alloy composition shown in Table 1 obtained by adding a specified metal to oxygen-free copper. In addition, the Ag content of the ingot is measured by the ICP emission spectrometry method described above. The ingot is processed in the following order to produce a rolled copper foil. In addition, the degree of processing in Table 1 is the thickness reduction rate in the final cold rolling, which is calculated by the following formula: degree of processing (%) = {(thickness before final cold rolling (mm) - thickness after final cold rolling (final product) (mm)) / thickness before final cold rolling (mm)} × 100.
[0190] <Steps (1) to (11)>
[0191] (Step 1) Homogenization annealing: The above ingot was heated at 920° C. and maintained for 2.5 hours.
[0192] (Step 2) Hot rolling: The ingot heated at 920° C. was rolled at room temperature to a thickness of 16 mm. Thereafter, the ingot was rapidly cooled to room temperature by water cooling to obtain a strip-shaped metal material.
[0193] (Step 3) Cold calendering 1: calendering to a thickness of 10.5 mm.
[0194] (Step 4) Recrystallization annealing 1: The strip-shaped metal material is heated at 400° C. and maintained for 7.5 hours.
[0195] (Step 5) Surface cutting: The oxide scale layer on the surface is removed by surface cutting.
[0196] (Step 6) Cold calendering 2: calendering to a thickness of 1.5 mm.
[0197] (Step 7) Recrystallization annealing 2: Maintain in a furnace heated to 750°C for 30 to 120 seconds.
[0198] (Step 8) Pickling and Polishing: After impregnation in a mixed acid of sulfuric acid and hydrogen peroxide water, the oxide film on the material surface is removed by performing polishing.
[0199] (Step 9) Cold Rolling 3: Rolled to a thickness of 0.8 mm.
[0200] (Step 10) Recrystallization Annealing 3 (Final Annealing): Adjust the annealing temperature and holding time to obtain a specified crystal grain size, and heat and hold the strip-shaped metal material after cold rolling 3 respectively. The annealing conditions of each specimen are described in Table 1. In addition, in order to prevent oxidation of the above strip-shaped metal material, a sealed body obtained by wrapping and sealing the strip-shaped metal material with a rolled copper foil (thickness: 33 μm) of fully annealed tough copper (JIS H 3100 (C1100)) is placed in a dryer. After heating and holding, the sealed body is taken out from the dryer and left to cool in the air atmosphere. After leaving to cool, the strip-shaped metal material is taken out from the sealed body. Then, by the above method, the average crystal grain size after the final annealing is measured.
[0201] (Step 11) Final Cold Rolling: Finish machining to a thickness of 0.012 mm (12 μm) to obtain a rolled copper foil. In the final cold rolling, the two end sides in the rolling direction of the strip-shaped metal material are not fixed (in a free-end state), and the strip-shaped metal material is passed between a pair of working rolls and rolled in such a way that the tension does not act in the direction parallel to the rolling direction.
[0202] In addition, in Examples 1 to 4 and Comparative Examples 1 to 3, recrystallization annealing 3 is carried out at the annealing temperature and holding time described in Table 1.
[0203] [Characteristic Evaluation]
[0204] [Evaluation of Taylor Factor]
[0205] Next, in Examples 1 to 4 and Comparative Examples 1 to 3, a portion of the rolled copper foil obtained by the above-mentioned manufacturing was taken as each test sample, and the test sample was sandwiched between two phosphor bronze (JIS H 3110 (C5210) standard) plates (thickness: 0.2 mm) to obtain a laminated body, and then the laminated body was wrapped and sealed with a rolled copper foil (thickness: 33 μm) of fully annealed tough copper (JIS H 3100 (C1100)) to obtain a sealed body, and the sealed body was placed in a dryer and heat-treated at a temperature in the dryer of 260° C. and a heating holding time of 30 minutes. After the heat treatment, it was taken out from the dryer and left to cool in the air atmosphere. After being left to cool, the rolled copper foil as the test sample was taken out from the sealed body. The sample surface of the heat-treated rolled copper foil was used as the measurement object, and the Taylor factor of the heat-treated rolled copper foil was measured by the scanning electron microscope (JSM-IT500HR) manufactured by JEOL Ltd. by the method described above. In addition, Tables 1 and 2 show the values and arithmetic mean of the Taylor factors of three points (any point N1, point N2 with a 5mm interval from N1 in the vertical direction of rolling, and point N3 with a 5mm interval from N1 in the vertical direction of rolling and in the direction opposite to the direction from N1 to N2) measured at 5mm intervals avoiding abnormal parts. N1 to N3 are rounded to the fourth decimal place, and the arithmetic mean is calculated based on the values rounded to the third decimal place, and are similarly expressed by the value rounded to the fourth decimal place. In addition, an attempt was made to measure the Taylor factor for the rolled copper foil after the final cold rolling and before the heat treatment at 260°C for 30 minutes. However, since the size of the subgrains and dislocation cell structure in the rolled structure was smaller than the step size (3 μm) of the EBSD measurement conditions, it was not possible to measure under the same conditions as the measurement conditions of the rolled copper foil sample after the heat treatment.
[0206] [Table 1]
[0207]
[0208] (Examination of Example 1)
[0209] By comparing Examples 1 to 4 with Comparative Examples 1 to 3, it was found that, on the basis of the final cold rolling processing degree being greater than 98% and less than 99%, the arithmetic mean value of the Taylor factor of the rolled copper foil after heat treatment at 260°C for 30 minutes can be controlled by appropriately setting the average grain size after the final annealing.
[0210] [Example 5, Comparative Examples 4-5]
[0211] In Example 5 and Comparative Examples 4 to 5, in order to confirm the relationship between the arithmetic mean of the Taylor factor and the bendability, rolled copper foils having the Taylor factors described in Table 2 were prepared for heat treatment at 260°C for 30 minutes. In addition, similar to the evaluation of the Taylor factor described above, the values and arithmetic mean of the Taylor factors at three points measured at intervals of 5 mm in the direction perpendicular to the rolling direction while avoiding abnormal parts were shown. The description of each value and the arithmetic mean is as described above. In addition, for the rolled copper foil before the final cold rolling and before the heat treatment at 260°C for 30 minutes, although an attempt was made to measure the Taylor factor, similar to Example 1, it was not possible to measure it under the same conditions as those for the specimens of the heat-treated rolled copper foil.
[0212] <IPC Slip Bend Test>
[0213] In Example 5 and Comparative Examples 4 to 5, a part of the rolled copper foil after the final cold rolling, that is, before the heat treatment at 260°C for 30 minutes, was taken as a test specimen for measurement. On one surface of the test specimen for measurement, after the roughening plating treatment was carried out with reference to the above-mentioned roughening plating treatment conditions, on the roughening plating treatment surface side of the rolled copper foil, Pixio (trademark) FRS grade (thickness 25 μm) manufactured by Kaneka Corporation, which is a polyimide resin film, was laminated, and press-bonded by a hot pressing treatment at 360°C for 30 minutes, thereby producing a single-sided copper-clad laminate composed of two layers of a rolled copper foil and a polyimide resin film. After that, using a known photolithography technique, wirings were formed such that the circuit width (Line) of the copper foil and the interval between adjacent circuits (Space) were Line / Space = 300 μm / 300 μm to produce an FPC. Then, a test piece was cut out from the obtained FPC in such a manner that the width was 12.7 mm, the length was 130 mm, and the length direction of the test piece was parallel to the rolling direction. Through Figure 1 the IPC (Institute of Printed Circuits) bend test apparatus 100 shown, the number of IPC slip bends of the test piece was measured. The IPC bend test apparatus 100 has a structure in which a vibration transmission part 20 is coupled to a vibration driving body 10, and the test piece 30 is fixed to the apparatus at a total of four points, that is, the part of the screw 40 indicated by the arrow and the tip of the vibration transmission part 20. When the vibration transmission part 20 is driven up and down, the middle part of the test piece 30 is bent into an arc shape with a specified radius of curvature r. Regarding the IPC slip bend test, it was carried out under the conditions that the radius of curvature r was 2.5 mm (outer radius), the vibration stroke was 20 mm, and the vibration speed was 1500 times per minute.
[0214] In addition, in the IPC sliding bending test, the number of times until the FPC breaks when bending is repeated under the above conditions is counted, and the number of test implementations under each condition is set to 4 times, and the IPC sliding bending test is implemented. The average value of the number of times until the break is obtained is used as the IPC sliding bending number and is shown in Table 2. In addition, the break mentioned here means that the electrical impedance of the FPC before the IPC sliding bending test has increased by 20%. The electrical impedance is measured by the 4-terminal method.
[0215] [Table 2]
[0216]
[0217] (Examination of Example 2)
[0218] Based on the comparison of the results obtained in Example 5 with the results obtained in Comparative Examples 4 to 5, it can be confirmed that when an FPC is made using a rolled copper foil in which the arithmetic mean of the Taylor factor measured after heat treatment at a dryer internal temperature of 260°C and a heating holding time of 30 minutes is controlled within a specified range, the FPC has better bendability than before.
[0219] In addition, the horizontal axis is the arithmetic mean of the Taylor factor of each sample in Table 2 after heat treatment at 260°C for 30 minutes, and the vertical axis is the result of IPC sliding bending times. Figure 2 In addition, the approximate straight line is calculated by the approximate curve straight line approximation function of Microsoft (registered trademark) Excel. Figure 2 The approximate formula of the straight line is shown together with the square of R. The closer the square of R is to 1, the more appropriately the approximate straight line shows the trend of the experimental data. It can be seen that there is a negative proportional correlation between the arithmetic mean of the Taylor factor after heat treatment at 260°C for 30 minutes and the number of IPC sliding bending times.
[0220] based on Figure 2 The approximate straight line of the IPC sliding bending times increased by more than 20% compared with the comparative example 4 as the existing product, that is, the arithmetic mean value of the Taylor factor after the heat treatment at 260°C for 30 minutes, which is more than 230,000 times of IPC sliding bending, was inversely converted to 2.4855. Therefore, it can be inferred that by using a rolled copper foil having an arithmetic mean value of the Taylor factor of 2.485 or less after the heat treatment at 260°C for 30 minutes, a rolled copper foil with higher bendability than before can be provided when FPC is formed.< / none> < / none> < / none>
Claims
1. A rolled copper foil containing 99.9 mass % or more of Cu, the remainder being composed of inevitable impurities, wherein when the rolled copper foil is heat treated at a temperature in a dryer of 260° C. and a heating holding time of 30 minutes, the arithmetic mean of the Taylor factors measured at a random point and two points in a direction perpendicular to the rolling direction, each of which is 5 mm apart from the point, is 2.485 or less. 2 . The rolled copper foil according to claim 1 , further comprising 100 to 360 mass ppm of Ag.
3. The rolled copper foil according to claim 1 or 2, which has a thickness of 4 to 35 μm.
4. The rolled copper foil according to any one of claims 1 to 3, wherein The arithmetic mean of the Taylor factor is greater than 2.
300.
5. A copper-clad laminate having a rolled copper foil having an arithmetic mean value of Taylor factors measured at 1 arbitrary point and 2 points equidistant from the point by 5 mm in a direction perpendicular to the rolling direction, i.e. 3 points in total, of 2.485 or less. 6 . The copper-clad laminate according to claim 5 , comprising a rolled copper foil having an arithmetic mean value of the Taylor factor of 2.300 or more.
7. A method for manufacturing a copper-clad laminate, comprising: A step of bonding the rolled copper foil according to any one of claims 1 to 4 to a substrate, and performing a heat treatment in the step.
8. A method for manufacturing a flexible printed wiring board, comprising: A step of using the copper-clad laminate produced by the method for producing a copper-clad laminate according to claim 7 as a material and forming wiring.
9. A method for manufacturing an electronic component, comprising: A step of manufacturing an electronic component including the flexible printed wiring board manufactured by the method for manufacturing a flexible printed wiring board according to claim 8.
Citation Information
Patent Citations
Bending resisting rolled copper foil
JP1992228553A
